MENJAGA AKAR TRADISI: MAKAN BAIDANG DALAM ACARA BADUA DI RANTAU SINGINGI, KABUPATEN KUANTAN SINGINGI, RIAU - Ariani, Fadhilah (Balai Pelestarian Nilai Budaya Kalimantan Barat, 2024)
This research explains the origins of the tradition of eating baidang in Rantau Singingi and details the procedures involved in the practice. It also offers an interpretation of the eating baidang tradition, discussing its importance in adapting to changing times, ensuring that the roots of this tradition remain intact and do not diminish over time. Using ethnographic methods, the study adopts a holistic and integrated approach, providing in depth descriptions and qualitative analysis to capture the community’s perspective that upholds this tradition. The findings indicate that eating baidang is a long-standing tradition continually practised by the Singingi community during badua (celebration) events. Serving food in this context is a way to extend hospitality to guests, underscoring the importance of respecting customs and empowering customary apparatus. The tradition of eating baidang follows specific rules regarding the order of serving the food, which trains discipline and reminds oneself of the stages that must be taken to achieve something. As time has changed, the practice of eating baidang has evolved; many now combine it with buffet-style dishes due to the extensive tableware required for a traditional eating baidang. While some may perceive it as outdated and troublesome, the tradition carries a deep meaning. It embodies critical social values such as gotong-royong (mutual cooperation), the value of politeness, and the strengthening of friendship while also providing a space for exchanging ideas.